P39 The acceptability and use of SMS text messaging for provider referral partner notification (PRPN). (23rd May 2012) - Gilbart, V; Town, K; Lowndes, C M
Abstract : Background: Partner notification is important for STI control. With developments in technology notifying partners is now easier. The HPA was keen to understand the acceptability and use of SMS texting for PRPN for STIs. Methods: A questionnaire distributed to GUM colleagues, cascaded by the Society of Sexual Health Advisers and posted on their website. Results: 65 sites responded. Most (61, 93%) use telephone for 1st attempt for PRPN with texting as preferred second choice (19, 29%). For 2nd attempt, telephone remained preferred method (51, 79%) but texting increased with 32 (49.2%) choosing this method; letter use also increased. Majority of sites used texting for PRPN (56, (86%); frequency varied—over half using it up to 50% of the time. 29 (45%) had texting guidelines and 31 (55%) used texting templates. Messages varied; 33 (59%) requesting partner make contact, 9 (16%) naming the infection. Six (11%) had contact with Information Governance Board about texting; no negative outcomes reported. Two partners complained, not about receiving a text but about being denied the identity of the index patient. 9 (14%) sites never used texting. Conclusion: Telephone contact was the preferred option for 1st and 2nd attempt for PRPN. Texting was the 2nd most used method and was seen as acceptable within the clinic and also with Information Governance Board. Frequency varied considerably and message content differed but even if used infrequently, was seen as important if other methods failed. Reassuringly no complaints about texting were received from partners. A small number of sites never use texting.